Penyuluhan Hukum Tentang Penghapusan Kekerasan Dalam Rumah Tangga Pada Jemaat Gereja Suli - Mahmud, Astuti Nur Fadillah; Corputty, Patrick (LPPI UMN AL WASHLIYAH, 2024)
ABSTRACT Introduction: Violence in the family environment is a social problem that is often encountered in Indonesia. This paper analyzes domestic violence that affects children, as well as other individuals in the household. Along with the birth of Law no. 23 of 2004 concerning the Elimination of Domestic Violence, the scope of this violence is even wider, including physical violence, psychological violence, sexual violence and neglect of the household.Purposes of Devotion: The main purpose of the service carried out is to provide views and understanding to the members of the Suli GPM Congregation regarding Law no. 23 of 2004 concerning the Elimination of Domestic Violence. So that members of the congregation can identify and avoid acts that can be categorized as domestic violence.Method of Devotion: The method used in this service activity is the method of legal counseling for the members of the Suli GPM Congregation which after the presentation of the material is followed by a question and answer session Results of the Devotion: In the lives of the members of the Suli GPM Congregation, there are still acts that can be categorized as domestic violence. Especially psychological violence, this often arises as a result of communication that is not built properly. Psychological violence often occurs not only to children and women, but this often happens on the contrary to a husband.